Problem Posing Approach to Optimization Creative Thinking Ability on Mathematics for Elementary Students - Bahtiar, Reza Syehma; Suryarini, Diah Yovita (Universitas Malikussaleh, 2019)
Mastery in creative thinking ability on Elementary school students have become a central issue in Indonesia education system. The ability to think creatively in learning Mathematics is needed in solving the problems, especially the problem in the form of stories. This study aimed to investigate the use of Problem Posing approach on creative thinking ability of elementary school students. The study is descriptive qualitative study. The students of fourth grade of elementary school were chosen as subject of the research. The data collected from the result of observation sheet and test and then analyzed using the scoring indicator rubrics, developed by Siswono. The result of this study showed that (1) By applying the problem posing approach, the activities of fourth grader elementary school students have increase in mathematics learning about the story problem on calculating mixed operations and (2) the application of the problem posing approach can improve the creative thinking ability of fourth grade students.